PENGARUH METODE DEMONSTRASI BERBASIS JARIMATIKA TERHADAP KEMAMPUAN BERHITUNGSISWA KELAS 3 DI UPT SPF SD NEGERI 106163 BANDAR KLIPPA - Santi Silaen; Perangin Angin, Laurensia Masri; Nurmayani; Elvi Mailani; Nurhudayah Manjani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this research is to determine the effect of the jarimatika demonstration method on the arithmetic abilities of students in class III C UPT SPF SD Negeri 106163 Bandar Klippa. The background of this research is the low arithmetic ability of students in basic operations, namely addition, subtraction, multiplication, and division. Students still experience difficulties in solving problems because they tend to use a one-by-one counting method, which often leads to calculation errors. This research was conducted using a quantitative approach with the Pre-Experimental Design method and the One Group Pretest-Posttest Design. The number of research subjects was 27 students from class III C UPT SPF SD Negeri 106163 Bandar Klippa. The data collection method used arithmetic skills tests and learning observations. Data analysis was conducted using the SPSS program with descriptive statistics and inferential statistics, including normality tests and Paired Sample t-tests. The results of this study indicate that the finger counting-based demonstration method has a significant impact on students' counting abilities. This is evidenced by the increase in the average student score from 47.19 on the pretest to 81.04 on the posttest. The results of the paired sample t-test showed a significance value of 0.000 (< 0.05), thus H₀ was rejected and H₁ was accepted. In addition, the standard deviation decreased from 24.61 to 9.42, indicating that the students' abilities became more uniform after the treatment. Therefore, it can be concluded that there is a significant influence of the finger arithmetic-based demonstration method on the counting ability of elementary school students